SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN PENERIMA BLT DENGAN KEMISKINAN EKSTRIM MENGGUNAKAN METODE WEIGHT PRODUCT PADA DESA KLAMBIR V KEBUN - Andhika, Nadya; Putra, Randi Rian (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Recently, the receipt of Direct Cash Assistance has not been on target, where only the poor have received the Direct Cash Assistance. The unequal distribution of direct cash assistance is caused by decisions that are difficult to consider due to manual data processing. For this problem, the researcher hopes to help the decision maker no longer have trouble making decisions in determining the recipients of this Direct Cash Assistance because of the existence of a decision support system. This decision support system uses many criteria that must be met by the recipient of the direct cash assistance. This decision support system uses the weight product method which can assist in making decisions in determining who is more appropriate to receive Direct Cash Assistance through the ranking results obtained from the results of calculations using the weight product method.